The American military mission to China, 1941-1942 : lend-lease logistics, politics and the tangles of wartime cooperation - Grieve, William G., 1937- (McFarland & Company, Inc., Publishers, 2014)
"Here is an overview of America's first effort in military aid to a foreign sovereign nation at a time when Europe was engaged in open warfare and Asia was undergoing a series of military confrontations"--